Sacral Nerve Stimulation Through the Sacral Hiatus - Park, Chan Hong (The Korean Pain Society, 2012)
Sacral nerve stimulation through the retrograde approach has been used for peroneal or irritable bowel syndrome through the retrograde approach. However, several reasons, lead could not be advanced down ward. In this case, anterograde sacral nerve stimulation through the sacral hiatus could be used. The aim of this report is to present of technique of sacral nerve root stimulation through the sacral hiatus approach.